Labor redundancy, retraining, and outplacement during privatization : the experience of Brazil's Federal Railway - Estache, Antonio 1957- (Policy research working paper, 2000)
When Brazil's Federal Railway was privatized, the team in charge of privatization made a significant effort to complement the incentive for voluntary reduction with an elaborate menu of training options. How did it work?